Boosting Psychological Well-being in One Session: A Rapid Counseling Approach to Digital Detox and Music Therapy - Oentarto, Aryobimo (Buletin Konseling Inovatif, 2026)
The rapid acceleration of technology has trapped modern youth in a digital connectivity paradox, where constant social media exposure triggers cognitive distortions and maladaptive behaviors that erode psychological well-being. This study evaluates the effectiveness of a Rapid Counseling approach integrated with Single-Session Music Therapy (RC-SSMT) in enhancing the psychological well-being of youth by breaking the cycle of digital addiction. Using a pre-test and post-test experimental design, the study focused on six youths (aged 15–17) at Church "X" in Jakarta who were identified as having low psychological well-being. The intervention combined a mandatory digital detox as a behavioral task with music therapy as a stimulus substitute, delivered in a single intensive session. Data were collected using Ryff’s Psychological Well-Being Scale (PWB-SQ) and analyzed using ANOVA. Statistical analysis revealed a highly significant improvement in psychological well-being scores (F(2, 10) = 108.824, p < .001). The Omega Squared value (ω2 = 0.956) indicated that 95.6% of the variance in well-being improvement was directly influenced by the RC-SSMT intervention. Follow-up data two months later showed that subjects successfully transitioned from "Less Well-Being" to the "Well-Being" category. The RC-SSMT model provides a practical, efficient, and adaptive solution for counseling practitioners to foster mental resilience and holistic well-being among Generation Z in the digital era.